Training, employee engagement and employee performance: Evidence from Uganda's health sector - Kasimu Sendawula; Saadat Nakyejwe Kimuli; Juma Bananuka; Grace Najjemba Muganga (Cogent Business & Management, 2018)
The purpose of this study was to investigate the contribution of training and employee engagement on employee performance using evidence from Uganda's health sector. This study is cross sectional and correlational. Usable questionnaires were received from 150 respondents from four Catholic founded hospitals that is Kamuli Mission Hospital, Buluba Mission Hospital, St. Benedict Mission Hospital and Budini Mission Hospital. Data were analyzed using SPSS. Regression analysis results indicate that training and employee engagement significantly predict employee performance by 44.7% and employee engagement was found to be a major predictor of employee performance as compared to training. Correlation analysis results indicate that there is a significant positive relationship between training and employee performance. Correlation analysis results further indicate that there is a significant positive relationship between employee engagement and employee performance. A partial mediation effect of employee engagement in the relationship between training and employee performance was also established. This research is important to managers, policy makers and Government in improving employee performance in the health sector. Given that this study was cross sectional, monitoring changes in behavior could not be possible. To the researchers' knowledge, this is the first study to establish the contribution of training and employee engagement on employee performance and at the same time provide an initial empirical evidence on the mediation effect of employee engagement in the relationship between training and employee performance using evidence from Uganda's health sector.
Keywords: 650